Joint stock company memorandum of association and environmental protection - Arsić, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
2011 Company Act stipulates that prevailing purpose of enterprise is mandatory element of memorandum of association. Connection between memorandum of association and environmental protection is based on provision that registration or doing certain business may be subject to license granted by relevant body. This is the case with 2009 Waste Management Act which provides for license granted by state authorities for doing one or more activities in waste management.